Hydrological modeling and transport of pollutants in water basins: A systematic review - Silva, Vinicius; Miranda, Everton; Lugon, Jader; Oliveira, Vicente; Silva, Simone; Santos, Giseli; Guimaraes, Édson; Silva Neto, Antônio (REVISTA CEREUS, 2023)
Environmental incidents around the world have been causing rapid deterioration of water quality, causing serious economic losses, impacting aquatic ecological environments and causing illness and death to surrounding residents. The precise determination of the surface water flow, based on the mathematical description of the hydrological processes on the natural basins, is of primordial importance for the evaluation of the impact of the transport of pollutants. This article intends to identify and map the main software used to study the trajectory of pollutants in watersheds, aiming to understand mathematical concepts, to identify the main methods and techniques used, as well as to verify the main contaminants studied by the scientific community today. The Method used of a systematic review protocol to gather evidence and support answers to research questions outlined with the help of the PICOC framework. On results was observed a convergence of authors to use the Soil and Water Assessment Tool (SWAT) software, either alone or in combination with other modules, to study the trajectory of pollutants. Among the studies, the predominance of pollutants was observed: Nitrate, Phosphate and Nitrogen, which suggests that these are the most studied substances today. The results presented in this article bring together and summarize the last decade of development in the field of studying the trajectory of pollutants in watersheds.